2021
DOI: 10.3389/fcvm.2020.588347
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of TGF-β/Smad Signaling in Cardiac Fibrosis: Non-coding RNAs as Effectual Players

Abstract: Unintended cardiac fibroblast proliferation in many pathophysiological heart conditions, known as cardiac fibrosis, results in pooling of extracellular matrix (ECM) proteins in the heart muscle. Transforming growth factor β (TGF-β) as a pivotal cytokine/growth factor stimulates fibroblasts and hastens ECM production in injured tissues. The TGF-β receptor is a heterodimeric receptor complex on the plasma membrane, made up from TGF-β type I, as well as type II receptors, giving rise to Smad2 and Smad3 transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 169 publications
3
65
1
Order By: Relevance
“…Numerous studies have demonstrated that TGFβ/Bmp signaling is involved in cardiac remodeling and HF [ 16 18 ], and have been determined to be the most affected pathways in Gsα CMKO mice. Bmp10 , a peptide growth factor, belonging to the TGFβ superfamily [ 19 ], is a differentially expressed gene that was found, through RNA-seq analysis, to be downregulated >threefolds.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that TGFβ/Bmp signaling is involved in cardiac remodeling and HF [ 16 18 ], and have been determined to be the most affected pathways in Gsα CMKO mice. Bmp10 , a peptide growth factor, belonging to the TGFβ superfamily [ 19 ], is a differentially expressed gene that was found, through RNA-seq analysis, to be downregulated >threefolds.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al [ 26 ] demonstrated that miR-503 expression was decreased in TGF-β1 stimulated lung fibroblasts and upregulation of miR-503 attenuated CAF-like myofibroblastic phenotype in myofibroblasts. Several miRNAs are involved in cardiac fibrosis (reviewed in [ 27 ]), and another study has proposed that miR-503 modulates fibrosis by enhancing the ECM deposition in cardiac fibroblasts [ 28 ]. miR-708 is one of the more recently discovered miRNAs to play a role in fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of the main AngII receptors, including the pro-inflammatory, pro-hypertrophic, and pro-fibrotic AT1 receptor, and the anti-inflammatory, anti-hypertrophic and anti-fibrotic type 2 (AT2) receptor were studied at the protein level [ 14 , 15 ] ( Figure 6 a–f). AT1 receptor was described to activate TGF-β, which can induce fibrosis via the canonical SMAD-dependent and the non-canonical SMAD-independent signaling pathways [ 14 , 15 , 26 ].…”
Section: Resultsmentioning
confidence: 99%